(untitled) (Universal International Scientific Journal, 2026)
This article discusses the importance of teachers’ competence in organizing the educational process in a qualitative and effective manner by integrating interactive methods, artificial intelligence tools, digital resources, various applications, and modern technologies into their teaching processes.